Cover, Volume 41, Issue 8. Issue 8 (27th July 2020) - Tunca, Ceren; Şeker, Tuncay; Akçimen, Fulya; Coşkun, Cemre; Bayraktar, Elif; Palvadeau, Robin; Zor, Seyit; Koçoğlu, Cemile; Kartal, Ece; Şen, Nesli Ece; Hamzeiy, Hamid; Özoğuz Erimiş, Aslıhan; et al.
Abstract : The cover image is based on the Data Article Revisiting the complex architecture of ALS in Turkey: Expanding genotypes, shared phenotypes, molecular networks, and a public variant database by Ceren Tunca et al., https://doi.org/10.1002/humu.24055 .